2020
DOI: 10.1242/jcs.250688
|View full text |Cite
|
Sign up to set email alerts
|

ESCRT recruitment by the S. cerevisiae inner nuclear membrane protein Heh1 is regulated by Hub1-mediated alternative splicing

Abstract: Misassembled nuclear pore complexes (NPCs) are removed by sealing off the surrounding nuclear envelope (NE), which is conducted by the ESCRT (endosomal sorting complexes required for transport) machinery. Recruitment of ESCRT proteins to the NE is mediated by the interaction between the ESCRT member Chm7 and the inner nuclear membrane protein Heh1, which belongs to the conserved LEM family. Increased ESCRT recruitment results in excessive membrane scission at damage sites but its regulation remains poorly unde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…We further find that Lem2 interacts via its MSC domain with another MTREC component, Iss10, although the physiological relevance of this interaction remains to be determined (see below). Together, this suggests that Lem2 employs a common mechanism for interaction with its downstream partners, which is in agreement with the MSC-dependent recruitment of members of the ESCRT pathways in NE repair and other functions reported for Lem2 homologs (Appen et al, 2020;Capella et al, 2020;Gu et al, 2017;Pieper et al, 2020;Thaller et al, 2019). Thus, Lem2 molecules may create a general recruitment platform at the INM for interaction with various partners.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We further find that Lem2 interacts via its MSC domain with another MTREC component, Iss10, although the physiological relevance of this interaction remains to be determined (see below). Together, this suggests that Lem2 employs a common mechanism for interaction with its downstream partners, which is in agreement with the MSC-dependent recruitment of members of the ESCRT pathways in NE repair and other functions reported for Lem2 homologs (Appen et al, 2020;Capella et al, 2020;Gu et al, 2017;Pieper et al, 2020;Thaller et al, 2019). Thus, Lem2 molecules may create a general recruitment platform at the INM for interaction with various partners.…”
Section: Discussionsupporting
confidence: 86%
“…CoIP assays were performed as previously described (Capella et al, 2020) with a few modifications in the lysis buffer, as follows. The lysis buffer contained 50 mM HEPES pH 7.4, 100 mM NaCl, 10% glycerol, 1 mM EDTA pH 8, 2.5 mM MgCl2, 0.5% NP-40, 1x complete EDTA-free protease inhibitor cocktail (Roche), 2 mM PMSF (Serva), 20mM N-ethylmaleimide (NEM, Sigma).…”
Section: Co-immunoprecipitation Assaysmentioning
confidence: 99%
“…2b ), revealing that CLIP formation is independent of cohibin integrity. In S. cerevisiae , HEH1 is a rare example of alternative splicing, which generates a shorter version known as Heh1-S that does not bind Nur1 28 , 29 . We consistently detected Lrs4 binding to Heh1, but not Heh1-S, upon expression of an N-terminal GFP-Heh1 fusion that allows detection of both splice variants (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous screen of the S. cerevisiae homozygous diploid deletion collection identified nine mutants that were more resistant than WT to 8% DMSO (115), none of which has any obvious functional relationship to endocytosis or membrane tension. However, a recent study found that chm7 Δ also confers improved colony growth in the presence of 4% DMSO, which presumably relates to Chm7’s function in membrane dynamics in the ER and nuclear envelope (116). Why loss of Chm7 would ameliorate effects of DMSO on membrane properties remains unclear.…”
Section: Resultsmentioning
confidence: 99%